The Federal Reserve, the Bank of England, and the rise of the Dollar as an international currency, 1914-1939 - Barry Eichengreen; Marc Flandreau (Graduate Institute of International and Development Studies, 2010)
This paper provides new evidence on the rise of the dollar as an international currency, focusing on its role in the conduct of trade and the provision of trade credit. We show that the shift to the dollar occurred much earlier than conventionally supposed: during and immediately after World War I. Not just market forces but also policy support - the Fed in its role as market maker - was important for the dollar's overtaking of sterling as the leading international currency. On balance, this experience challenges the popular notion of international currency status as being determined mainly by market size. It suggests that the popular image of strongly increasing returns and pervasive network externalities leaving room for only one monetary technology is misleading.
Keywords: 330; US-Dollar; Reservewährung; Geldpolitik; USA